GRAIN FILLING DEVICE - Swapana Mahadev Vasekar 1, Vishal Mahadev Nagane2, Abhijeet Sujit Kshirsagar2, Yashraj Navnath Kale2, Ritesh Shashikant Dhavare 2 (International Journal of Innovations in Engineering Research and Technology, 2022)
A simple manually operated grain collector and bagging made of locally available materials using local manufacturing technology was designed, fabricated, and tested for collecting and bagging of grains(paddy) dried on concrete pavement. The invention belongs to the technical field of agricultural machines, and relates to a tool applied when grains are collected after being aired, in particular to a manual grain bagging machine. Grains are automatically loaded into a dustpan by pushing the manual grain bagging machine with hands, a hand wheel of a drive assembly is rotated so that a gear can push a rack to move upwards at first and then move horizontally, and a stop bar on the dustpan is blocked by a left arc baffle and a right arc baffle so that the dustpan can tilt to pour the grains into an opening bag. A simple manually operated grain collector and bagging had the following major components: frame, wheel, long pipe, vertical stand frame (bars), horizontal bars, collector, and bag. Radial flat bladed type base plate, slot bar, sweeping box, bagging area, frame and the conveyance system. Results showed significant differences on the collecting capacity, and noise level. Other parameters such as collecting efficiency, air velocity, augmented cracked grain percentage. The design was made based on certain assumptions and calculation and the collector was built tested and evaluated.